Does the Rise of China Lead to the Fall of European Welfare States? - Erling Barth; Henning Finseraas; Anders Kjelsrud; Karl Ove Moene (Institute of Labor Economics (IZA), 2021)
Have recent trends in globalization changed the positive link between trade openness and social insurance? The consensus view - that voters want better social insurance against income loss the more open the economy - is seemingly contested by the rise of populism and the China shock. We present a theoretical framework of risk and income effects of globalization that captures the conventional view, but also shows when it will be modified: When the income effect is negative, the political support for social insurance can decline in spite of the risk effect. We construct an empirical measure of welfare state support across European regions and leverage the rapid integration of China into the world economy to show that higher import competition reduces the support for social insurance. Consistent with our framework, we decompose the overall effect of the shock into a (weak) positive risk effect and a (strong) negative income effect.
Keywords: J21; J23; H35; H55; F16; F6; 330; regional labor demand; welfare state support; social insurance; China shock; trade exposure